The Effect of Corrupt Market Experience on FDI: Evidence from Swedish Manufacturing Enterprises - Suanna Thede; Patrik Karpaty (Örebro University School of Business, 2021)
In this paper, we analyze if the enterprise decision to invest in a corrupt market is affected by its experience of other corrupt markets. Our conjecture is that multinational enterprises (MNEs) can learn how to navigate corrupt environments and reduce their corruption-related market entry costs. We test this conjecture using a rich data set on manufacturing enterprises from an uncorrupt country, Sweden, over the 1997-2015 period. The market entry effect of corrupt country experience is examined using an extended gravity model (Morales et al., 2019) controlling for income group, regional and border country experience. We find strong support of our conjecture using mixed logit estimations, which are consistent with the multidimensional entry decision of the extended gravity model. To understand the effect of corruption on foreign direct investment, the outreach pattern of MNEs needs to be taken into account.
Keywords: F23; 330; Corruption; multinational enterprise; foreign direct investment